Estudo das percepções de usuários e bibliotecárias na biblioteca da Universidade Federal de Viçosa - Rodríguez Antúnez, Evelin (1987)
This study discusses the technical and administrative failures at the Library of the Universidade Federal de Viçosa - UFV (Minas Gerais, Brazil), through an analysis of perceptions of faculty and librarians. It includes the opinions about library service, the user librarian interaction, professional performance of librarians, activities, and problemas affecting library performance. The review of the literature includes studies on faculty and librarians' perceptions at university libraries and studies on conflicts in libraries. The research methodology is fully presented, including the techniques for content analysis and interviewing applied in the studies of faculty and librarians. The main contribution is an analysis of the occasions where conflict arises as consequences of technical/administrative disfunctions. Finally, results and conclusions are presented, and recommendations are mad to solve the conflicts at the Library of UFV.